ANALISA DAN PERANCANGAN SISTEM INFORMASI PENCATATAN KEGIATAN PEMBANGUNAN SARANA & PRASARANA PADA PROGRAM KOTAKU BERBASIS GIS DENGAN GMAPS DI BKM KELURAHAN SUNGAI LANGKAI: Geographic Information System; Google Map; Facilities and infrastructure; KOTAKU; E-Government - Hidayat, Fendi (JURNAL AKADEMIKA, 2018)
The process of recording the construction of facilities and infrastructure in the BKM Langkai is carried out conventionally. This makes it very difficult for the community to see the development and benefits of the development program. To support the transparency process and to monitor the development progress of the KOTAKU program, it is necessary to develop a computerized Information System to process the recording of the construction of facilities and infrastructure in the KOTAKU program or inventory. It is expected that this information system can help BKM Sungai Langkai in recording every construction of facilities and infrastructure and can be used by the community to see and monitor the direct development of the process of building facilities and infrastructure carried out in the KOTAKU program at BKM Sungai Langkai. So that it can help implement transparency in the process of implementing development activities.